Clinical effectiveness of various treatments for cartilage defects compared with microfracture: a network meta-analysis of randomized controlled trials - Sathish Muthu; Vibhu Krishnan Viswanathan; Girinivasan Chellamuthu; Mohammad Thabrez (Elsevier, 2024)
Background: Advancements have been made in the realm of cartilage-regenerative techniques in the past decades. However, their comparative advantage has not yet been fully studied. Objectives: To comparatively analyze the functional, radiological and histological outcomes, and complications of various procedures available for the treatment of cartilage defects. Data sources: PubMed, Embase, Web of Science, Cochrane, and Scopus. Study eligibility criteria, participants, and interventions: Randomized controlled trials reporting functional, radiological, histological outcomes, or complications of various methods were utilized in the management of cartilage defects. Patients with cartilage defects. Treatment methods include microfracture (MFX), autologous chondrocyte implantation (ACI), osteochondral allograft/autograft transplantation (OAT), mosaicplasty, or acellular implants. Study appraisal and synthesis methods: Cochrane's Confidence in Network meta-analysis approach. Network meta-analysis was conducted in Stata. Random effects model was used for forest plots. Results: Three thousand one hundred ninety-three patients from 54 randomized controlled trials were included in the analysis. The mean age of included patients was 37.9 (±9.46) years. MFX-I was used as a constant comparator. Among the restorative methods, OAT-II offered significantly better functional outcome at 5 years (weighted mean difference [WMD] = 16.00, 95% confidence interval [CI] [11.66, 20.34], P < .001) and 10 years (WMD = 16.00, 95% CI [10.42, 21.58], P < .001), while OAT-I offered significantly better pain relief (WMD = −1.74, 95% CI [−3.45, −0.02], P = .042), and retained hyaline histology (odds ratio = 8.12, 95% CI [4.17, 12.07], P = .001) at 1 year with least-reported adverse events and failures. Among the regenerative methods, MFX-III (WMD = −10.0, 95% CI [−13.07, −6.93], P = .008) offered significantly better functional outcomes at 5 years, while ACI-III (odds ratio = 0.89, 95% CI [0.03, 1.76], P = .032) demonstrated significantly better radiological outcomes at 2 years. Limitations: Heterogeneity in reporting of diverse functional outcome measures. Conclusions and implications of key findings: Compared with MFX-I, OAT-II demonstrated significantly better long-term functional outcome (10 years), while ACI-III and MFX-III demonstrated significantly better functional outcomes only till midterm (5 years), and there is a paucity of long-term data on these treatment methods. Systematic review registration number: CRD42022338329.